The Relationship Between Degrees of Myopia and Intraocular Pressure at dr. Wahidin Sudirohusodo Mojokerto Hospital - Rini Kusumawar Dhany; Tiara Alifiyah; Kartika Prahasanti (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2026)
Myopia is a common refractive disorder, and its prevalence continues to rise globally, including in Indonesia. In young adults over 21 years of age, the prevalence of myopia with a refractive error greater than -0.5 D reaches 48.1%. Myopia has been associated with various ocular complications, including elevated intraocular pressure (IOP), which can lead to further vision impairment. This study aims to analyze the relationship between the degree of myopia and intraocular pressure in myopic patients. A cross-sectional and consecutive sampling of myopia patients at Dr. Wahidin Sudirohusodo Hospital. Data from medical records and direct examination. Chi square correlation analysis revealed a significant relationship between the degree of myopia and intraocular pressure. In the right eye, the p-value was 0.03 (p < 0.05), while in the left eye, it was 0.01 (p < 0.05). Patient characteristics showed that the majority were female (69.6%), and most patients were young adults aged 21–40 years (79.7%). There is a significant relationship between the degree of myopia and intraocular pressure at Dr. Wahidin Sudirohusodo hospital.